2013
DOI: 10.1007/s10162-013-0375-2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Evidence for Possible Simultaneous Induction of Hyperacusis and Tinnitus Following Intense Sound Exposure

Abstract: Many human subjects suffering from chronic tinnitus also suffer from hyperacusis, a heightened perception of loudness at moderate to intense sound levels. While numerous studies suggest that animals develop chronic tinnitus following intense noise exposure, it is not yet clear whether sound exposure also induces chronic hyperacusis-like responses in animals. We addressed this question by examining the chronic effects of intense sound exposure on the acoustic startle response (ASR) and its suppression by backgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
71
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 39 publications
12
71
1
1
Order By: Relevance
“…Enhanced startle response amplitudes and/or lower startle thresholds, suggestive of hyperacusis, have been reported in animals with hearing loss induced by salicylate (Sun et al 2009), aging (Ison and Allen 2003), or noise (Chen et al 2013). In these studies, startle amplitudes were elevated at all levels above startle threshold.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Enhanced startle response amplitudes and/or lower startle thresholds, suggestive of hyperacusis, have been reported in animals with hearing loss induced by salicylate (Sun et al 2009), aging (Ison and Allen 2003), or noise (Chen et al 2013). In these studies, startle amplitudes were elevated at all levels above startle threshold.…”
Section: Discussionmentioning
confidence: 60%
“…The magnitude of tone-or noise-burst PPI can be a useful measure of stimulus detectability (Hoffman and Ison 1980). These startlebased responses are often enhanced after systemic administration of salicylate (Yang et al 2007) and can be enhanced after noise-induced temporary or permanent threshold shift (Chen et al 2013;Sun et al 2012), manipulations known to induce central auditory hyperactivity in animal models (for review, see Kaltenbach 2011 andEggermont 2013). Consequently, these overreactions to sound are interpreted as behavioral signs of hyperacusis.…”
mentioning
confidence: 99%
“…Recent animal studies have shown increased hyper-responsiveness and startle behavior induced by noise exposure causing degeneration of the cochlear nerve [18][19][20]. Hyperacusis and tinnitus often occur together, and studies have confirmed the involvement of peripheral neural degeneration in the development of both symptoms [8].…”
Section: Discussionmentioning
confidence: 96%
“…While the two pathologies can be easily assessed and distinguished in humans based on direct symptomatology reports and answers to scientifically designed questionnaires, the equivalent evaluations in animal models are challenging. One way of discriminating between the elevated gains due to tinnitus and hyperacusis could be to rely on the assumption that hyperacusis animals should show elevated startle amplitudes and/or elevated normalized prepulse inhibition (Chen et al 2013) across multiple frequencies of the sound stimulation, as hyperacusis is not frequency specific. However, no such pattern could be established in our data.…”
Section: Tinnitus and Hyperacusismentioning
confidence: 99%